GALVÁN, V. (2024). Así habló Juan de Mairena: cantares de un filósofo. Granada: Editorial Comares - Vázquez García, Francisco (Daimon Revista Internacional de Filosofia, 2026)
Reseña de GALVÁN, V. (2024). Así habló Juan de Mairena: cantares de un filósofo. Granada: Editorial Comares